ACTOR SEQUITUR FORUM REI: A THEORITICAL STUDY - Sujayadi, Sujayadi; Wijayanta, Tata; Herliana, Herliana (Jurnal Bina Mulia Hukum, 2023)
The actor sequitur forum rei principle is the primary basis for determining the relative competence of civil courts in countries that adopt civil law systems. In this article, the role of the actor sequitur forum rei will be examined theoretically by analyzing theories related to personal jurisdiction, categorization of jurisdiction, and procedural justice theory. The analysis results indicate that actor sequitur forum rei is founded on the theory of power and is classified as a "connected" jurisdiction with a general nature, as jurisdiction is linked to the defendant's domicile. It enables the defendant to be sued in the forum of their domicile at any time and for any reason. Additionally, according to procedural justice theory, actor sequitur forum rei is shown to provide the defendant with protective aspects.